Clinicopathological Spectrum and Treatment Outcome of Clinically Suspected Rapidly Progressive Glomerulonephritis: An Analysis of 35 Cases in a Tertiary Care Center, Bangladesh - Roy, Ranjit Ranjan; Arju, Jahanara; Sultana, Jakia; Rahman, Farhana; Hasan, Mohammad Imrul; Mamun, Abdullah Al; Jesmin, Tahmina; Huque, Syed Saimul; Begum, Afroza; Uddin, Golam Muin; et al. (Journal of Pediatric Nephrology, 2019)
Background and Aim: Rapidly progressive glomerulonephritis (RPGN) is characterized by a rapid decline in the renal function and urinary abnormalities. There is limited information on epidemiological factors and clinical and histopathological patterns of RPGN from developing countries. Therefore, the objective of this study was to identify the etiology, clinical features, histopathological patterns, and treatment outcomes of patients with clinically suspected RPGN. Methods: This retrospective study was conducted in the Pediatric Nephrology Department of Bangabandhu Sheikh Mujib Medical University from January 2014 to January 2019. Patients with clinically suspected RPGN that underwent renal biopsy were enrolled in this study. Results: Thirty-five patients were recruited in this study. Macroscopic hematuria, edema, hypertension, uremia, and oliguria were common clinical presentations. Diffuse proliferative GN (28.5%) and crescentic GN (22.8%) were the most common histological diagnoses in this study. Immune mediated GN (62%) followed by idiopathic GN (25%) were found to be the most frequent cause of crescentic GN. Renal replacement therapy was required in 45% of the cases and 11.4% of the patients developed end-stage renal disease. Conclusion: Renal histology is an integral part of the investigation of patients with suspected RPGN for both diagnostic and prognostic purposes. Diffuse proliferative GN was the most common histopathological diagnosis in patients with clinical RPGN in our population. Preservation of renal function depends on early intervention and detection of RPGN in pediatric patients. Keywords: Nephritis; Glomerulonephritis; ESRD; End-Stage Kidney Disease; Child.